PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE PADA KEMENTERIAN AGAMA KOTA PALEMBANG - Surtiningsih, Wati; Sapitri Menghayati, Oki; Azizah, Nur; Amelia Putri, Helen; Tarissyaa, Uut; Rahmawati, Tri Putri; Hafizzallutfi, Hafizzallutfi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research is entitled Implementation of the Principles of Good Corporate Governance at the Ministry of Religion of Palembang City. The problem in this study is how the Implementation of the Principles of Good Corporate Governance at the Ministry of Religion of Palembang City. The purpose of the study was to determine how the Implementation of the Principles of Good Corporate Governance at the Ministry of Religion of Palembang City. This research method uses qualitative research with a descriptive approach. To understand the central symptom, researchers interviewed research participants or participants by asking general and rather broad questions. The object of research is how the application of the principles of Good Corporate Governance at the Palembang Ministry of Religion Office. The sampling technique is purposive sampling where the researcher determines the sampling itself by determining the sample that is considered to have key information in this research. The subject of this research is the Head of Administration of the Office of the Ministry of Religious Affairs Palembang City. The data collection techniques used are surveys, interviews, and documentation. The results showed that this study analyzed the implementation of the principles of Good Corporate Governance (GCG) at the Palembang City Office of the Ministry of Religious Affairs. Through a comprehensive approach, this research explores the implementation of GCG principles in the context of government institutions, highlighting the strategies, policies and mechanisms implemented by the Ministry of Religious Affairs to improve transparency, accountability and efficiency in resource management. The research provides an in-depth understanding of the challenges, opportunities and impacts of GCG implementation within local government institutions, and provides recommendations for further improvement.